Sperm Competition and Paternity in the Endangered Firefly Pyrocoelia pectoralis (Coleoptera: Lampyridae: Lampyrinae) - Xinhua Fu; Victor Benno Meyer-Rochow; Lesley Ballantyne; Xinlei Zhu; Qiyulu Zhang (Insects, 2024)
The endangered terrestrial firefly Pyrocoelia pectoralis (Olivier) is endemic to China. Populations of P. pectoralis have decreased dramatically due to urbanization and pollution. Breeding and re-introduction to a suitable habitat may save the species from becoming extinct. Because of its polyandrous character, an investigation into the possibility of sperm competition and paternity outcomes from multiple matings was initiated to better understand its reproductive physiology. To achieve these goals, 13 SSR markers were developed. The results of paternity experiments indicate there is a significant difference between P3 and P1 or P2. The female reproductive system has three spermathecae which accept sperm from different matings, and no bursa or spermatophore-digesting organ is developed. Our research established that multiple inseminations with sperm from different males occur, leading to competition between ejaculates. The benefits of such competition include an increasing number of sperm in the ejaculates of competing males and the consequential increase in fertilized eggs (thus, fecundity), and thereby a higher chance of genetic diversity and fitness in the offspring of the firefly P. pectoralis.